KOMUNITAS MILLAH ABRAHAM: PERKEMBANGAN AJARAN DAN PERSEBARANNYA DI HAURGEULIS INDRAMAYU - Asnawati Asnawati (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2015)
Millah Abraham community is also called Komar. It expands and develops in Haurgeulis, Indramayu, West Java. The community is considered to deny Prophet Muhammad because they believe Ahmad Mushaddeq and call him Al-Masih Al-Maw’ud. Their scripture is “Ruhul Kudus”. Indonesian religious affairs council (MUI) says that this community has deviant and false ways. This study has purpose to discover who bring and spread out Komar doctrine in Haurgeulis and how his background is. The other aim is to investigate its development and influence in the society. This research is conducted in the Haurgeulis, Indramayu and the subjects are Komar followers who become the victims. The research employs qualitative approach and the data collection consists of interviews, observation, and document. The result shows that Komar is eventually dismantled and its followers are saved by the local apparatus.